Perioperative optimization and right heart catheterization: what technique in which patient? - De Backer, Daniel (BioMed Central, 2003)
Recent years have seen the place of the pulmonary artery catheter in intensive care increasingly challenged, with one recent study reporting no difference in outcome in patients treated with or without a pulmonary artery catheter. However, this study has several methodological flaws and, although pulmonary artery catheterization should not be performed routinely on all patients, when used correctly by trained personnel in selected patients the pulmonary artery catheter continues to provide valuable information.